International law : a very short introduction - Lowe, A. V. (Alan Vaughan) ([Oxford] : Oxford University Press, 2015)
International law lies at the heart of our interaction with the global community. It protects rights, imposes duties, and establishes a framework for the conduct of almost every social, political, and economic activity. Vaughan Lowe explains the basic structural principles of international law, and looks at its potential and its limitations.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on November 12, 2015).
Keywords: International law